Conceptualizing Employer-Based Brand Equity and Employer Brand Pyramid - Kashive, Neerja; Khanna, Vandana Tandon (European Scientific Journal, ESJ, 2017)
Employer branding is referred to as a firm's efforts to promote, both within and outside the firm, a clear view of what makes it different and desirable as an employer. It constitutes an important concept in today's knowledge intensive contexts where attracting employees with superior skills and knowledge comprises a primary source of competitive advantage. This research paper will focus on building employer brand equity by exploring the previous research on employer brand. Based on the Keller brand pyramid this is an attempt to build similar pyramid for employer brand and see if same concepts of customer based brand equity can be used to conceptualize the idea of employer based brand equity. This will help the organizations to understand the ways to build strong employer brand to attract and retain better talent in their organizations.